Thermal effects of plume impingement on a hypersonic vehicle - Hillyer, J; Doherty, L; Estruch-Samper, D; Barth, J; McGilvray, M (Council of European Aerospace Societies, 2022)
The thermal effects of plume impingement on the uselage of a hypersonic vehicle were investigated using a plume generator mounted to a flat plate model in the Oxford High Density Tunnel at Mach 7. The model was instrumented with thin film heat transfer gauges, pressure transducers, Pressure Sensitive Paint and thermocouples. Schlieren photography was used to visualize the flowfield. Exit Pressure Ratios of up to 22 were tested, with CO2 as the cold injected gas. Three nozzles were used to explore the effect of changing the expansion profile on heat transfer: a 5 mm conical nozzle, a 6 mm conical nozzle and a 6 mm Rao nozzle. It has shown that initially Stanton number decreases by up to 90% with cold gas injection, but flow separation causes the Stanton number to increase up to 125% of the no injection condition. This significant decrease in heat transfer indicates that there will be direct contact between the rocket engine plume and the fuselage, allowing for significant heat transfer to the fuselage.